PELATIHAN LARI-LOMPAT RINTANGAN LEBIH BAIK DARIPADA PELATIHAN LARI-LOMPAT KE DEPAN DALAM MENINGKATKAN HASIL LOMPAT JAUH PADA SISWA SMAN-2 MENGWI BADUNG - I Made raka; Ni ketut ayu juliasih (Sport and Fitness Journal, 2015)
This study aimed to determine the training method to improving long jump results of two training methods. Research conducted on 24 students of SMAN-2 Mengwi Badung and divided by into two groups. One group was given run-jump obstacle training and two groups was given run-jump ahead training. The data obtained were analyzed by paired ttest to determine the difference between before and after training in both groups and independent t-test to test the difference in long jump results between groups after training. The results of statistical test, an increase in the long jump results between before and after training in group-1 of 441.67 ± 34.40 cm to 507.50 ± 34.08 cm with a value of p < 0.05 (significantly different) and on -second group increased from 444.58 ± 31.58 cm to 478.33 ± 32.64 cm with a value of p